ANALISIS AKAD MUSYARAKAH MUTANAQIṢAH DALAM FATWA DNS-MUI DAN PERATURAN PERBANKAN SYARIAH - Sawaluddin Siregar; Hendra Gunawan (Yayasan Baitul Hikmah al-Zain, 2025)
The problem in this study is that mutant musyᾱrakah should be aimed at financing with a productive character such as working capital, not consumptive such as mortgage financing. Because of this, there are several perceptions in the public that there is a discrepancy between fatwa and SEBI/SEOJK regulations. This research is a library research, the problem approach method used, the ushuliyah rule approach and the siyasah syar'iyah approach. The data source comes from everything that has been processed and politicized in the form of official documents, books/books, and scientific journals related to the mutant musyᾱrakah contract as an object of research with a qualitative analysis method with an inductive thinking method. The results of this study found that the implementation of mutant mutakah mutakah contracts, the author found that this is in accordance with the concept of Islamic law even though it has been transformed into SEBI and SEOJK, mutant mutant mutakah is shown to be productive and non-consumptive because in it there are rental activities of capital participation between banks and customers.